Sistem Monitoring Kualitas Air Kolam Ikan Koi dan Kontrol Berbasis IOT - Anggagana, Dwi Gita; Charis Fathul Hadi; Ratna Mustika Yasi (ZETROEM, 2025)
Koi fish is an ornamental fish with a considerable quantity of enthusiasts among the upper middle class. This makes the koi ornamental fish business widely developed because the value of the market price is quite high compared to some other types of ornamental fish. Koi farming is quite complicated to make its own problems in the conduct of koi fish farming. The number of variables that affect the growth, health, as well as the pattern and color of the fish makes treeger distinctive for some people to develop effective and efficient technology in the cultivation of ornamental fish species of koi. One of the benefits of developing technology to optimize koi fish farming by conditioning the feasibility of pond water using IoT in monitoring water conditions in koi ponds. Monitor pH and density using sensors in the water which is also a variable that affects the health and color and pattern enforced by utilizing microcontroller Esp 8266 and arduino uno R3 as the brain of the system. The prototype test was carried out by providing two treatments for water, namely acid and alkaline treatment of the pH value and water concentration to be adjusted. Prototype testing results provide satisfactory results compared to manual measurements. "Koi pond water quality Monitoring system and IOT-based automatic control" proved to function well to condition the pH and water density (ppm) so that it is assumed to improve the management of koi fish farming because of its automated system work and ease of technical monitoring.